Selective electrochemical detection of 2,4,6-trinitrotoluene (TNT) in water based on poly(styrene-co-acrylic acid) PSA/SiO2/Fe3O4/AuNPs/lignin-modified glassy carbon electrode - Mahmoud, Khaled A (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
A new versatile electrochemical sensor based on poly(styrene-co-acrylic acid) PSA/SiO2/Fe3O4/AuNPs/lignin (L-MMS) modified glassy carbon electrode (GCE) was developed for the selective detection of trace trinitrotoluene (TNT) from aqueous media with high sensitivity. The fabricated magnetic microspheres were characterized by transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). L-MMS films were cast on the GCE surface to fabricate the TNT sensing electrode. The limit of detection (LOD) of TNT determined by the amperometric i-t curve reached 35 pM. The lignin film and well packed Fe3O4/AuNPs facilitated the pre-concentration of trace TNT on the electrode surface resulting in a fast amperometric response of 3 seconds near the detection limit. The high sensitivity and excellent catalytic activity of the modiﬁed electrode could be attributed to the lignin layer and highly packed Fe3O4/AuNPs on the electrode surface. The total recovery of TNT from tapwater and seawater matrices was 98% and 96%, respectively. The electrode film was highly stable after five repeated adsorption/desorption cycles. The new electrochemical sensing scheme provides a highly selective, sensitive and versatile assay for the in-situ detection of TNT in complex water media